2004
DOI: 10.1203/01.pdr.0000114481.58902.fb
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Exercise-Induced Arterial Hypoxemia in Prepubescent Trained Children

Abstract: Exercise-induced arterial hypoxemia (EIAH) is a recognized phenomenon in highly trained adults. Like adult athletes, prepubescent trained children may develop high-level metabolic demand but with a limited lung capacity in comparison with adults. The purpose of this investigation was to search for evidence of EIAH in prepubescent trained children. Twenty-four prepubescent (age: 10.3 Ϯ 0.2 y) trained children (10.0 Ϯ 0.7 h of weekly physical activity) performed pulmonary function tests and a graded maximal exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…herein is whether children who demonstrate EIAH (27) can perform the two-test protocol successfully. This was because all children maintained arterial oxygenation throughout the tests and thus, the possibility that EIAH might contribute to fatigue and preclude an individual from cycling for sufficient duration at 105% of the peak IWT power cannot be dismissed at this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…herein is whether children who demonstrate EIAH (27) can perform the two-test protocol successfully. This was because all children maintained arterial oxygenation throughout the tests and thus, the possibility that EIAH might contribute to fatigue and preclude an individual from cycling for sufficient duration at 105% of the peak IWT power cannot be dismissed at this time.…”
Section: Discussionmentioning
confidence: 99%
“…What has not been established in children is whether this procedure is effective across the spectrum of lower fitness levels as might be expected in a randomly recruited population, for example, in the United States. It is also pertinent that among this population of prepubescent children there may be a high prevalence of expiratory flow limitation (EFL, 28,29,40) and possibly exercise-induced arterial hypoxemia (EIAH,27). Whether the two-test protocol can effectively determine VO 2 max across a broad spectrum of fitness levels and in the presence of EFL in children which, in and of itself may increase fatigability and modulate the respiratory response to exercise, has not been determined.…”
mentioning
confidence: 99%
“…VE and . VCO 2 recorded between the onset of exercise and the occurrence of the respiratory compensation point (Nourry et al, 2004;Deruelle et al, 2006). The respiratory compensation point, i.e.…”
Section: Ventilatory Response To Exercise Measurementsmentioning
confidence: 99%
“…16 The oxygen saturation decrement with oxymetry pulse measurement may imply exercise-induced hypoxemia. 17 A study found that hypoxemia occurs when SpO 2 is decreasing from 97% to 92%. 18 Another study also reported that minor exercise-induced hypoxemia may occur when the SpO 2 decreases to 93-95% (3-4%) since resting, from resting with the moderate occurs in 88-92% since resting and the major one occurs when a decrease from 88% happens.…”
Section: Discussionmentioning
confidence: 99%